SATIRE LANGUAGE STYLE BY BU TEJO IN THE SHORT FILM “TILIK” - Ayuningtyas, Nawang Asri; Triyono, Sulis (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
The use of satire language style by a film creator aims to convey meaning to the public. This study aims at analyzing the use of satire language styles used by Bu Tejo in a short film entitled "Tilik." This research used a qualitative descriptive method. The object of this research is satire utterances spoken by Bu Tejo in the film "Tilik." The data collection techniques in this study used observation, listening, and note-taking techniques. The results demonstrate three types of satire languages used by Bu Tejo in the film “Tilik": cynicism, irony, and sarcasm. It is also found that cynicism is the most spoken language than sarcasm. The study highlights that the use of satire language uttered by Bu Tejo aims to convey ideas and perspectives related to problems occurring in society and express dissatisfaction.